Segmental Aspects of Pronunciation Errors Produced by ELE Students in Classroom Settings - Sandy Vitra Nugraha; Lalu Ari Irawan; Haerazi; Tina Orel Frank (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2022)
Pronunciation plays important roles in making the intelligibility of a speech. In pronunciation, speech and gesture production are interrelated and coordinated. Not all language learners can pronounce English words well. Learners make errors while speaking English. It make them not confident to pronounce other English words. Therefore, this study aims to identify students’ segmental aspects of pronunciation errors in classroom setting. This study is categorized as qualitative study to understand phenomena using data such as interviews, observations, and documents reviews to identify and interpret specific characteristics of the material to learn human behavior. The population of this research is the sixth-semester students of English department at Mandalika University of Education, Mataram-Indoneisa. This research used purposive sampling method that engaged of 6 students as the sample of the data. The students divided by 2 criteria: Gender and pronunciation level. To make the data valid, all the students has passed 3 stages of pronunciation level. The result of this study indicated that all the subjects are difficult in pronounced consonant /f/ sounds and still need improvisation in a short vowel sound because the student’s errors are divided into 3 categories; psycholinguistic, sociolinguistics, and Epistemic sources. Furthermore, this study proves that “man smart, woman smarter.